Association of Genetic Polymorphism TP53INP1 Gene with Mineral Content in Javanese Thin-Tailed Sheep - Listyarini, K.; Harahap, R. S.; Roosita, K.; Sumantri, C.; Mulyono, R. H.; Gunawan, A. (Universitas Bengkulu, 2025)
The Tumor Protein P53 Inducible Nuclear Protein 1 (TP53INP1) gene is expected to be a crucial candidate for mineral content. This research aimed to analyse the genotype polymorphism and investigate its association with the TP53INP1 gene and sheep mineral content. To analyse gene polymorphisms and conduct an association study, 30 rams of Javanese thin-tailed sheep were utilised. The NlaIII restriction enzyme was applied to investigate the genotype polymorphism of the TP53INP1 gene through Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). Regarding the association with analysing TP53INP1, a General Linear Model (GLM) was used. The findings indicate that the TP53INP1 gene shows polymorphism, revealing three distinct genotypes identified by the results: AA, AG, and GG. The genotypes were detected using the Hardy-Weinberg Equilibrium (HWE) principle. According to the association analysis, a significant association (P < 0.05) was found between the TP53INP1 gene and mineral content, particularly iron (Fe). A higher mineral content was associated with the GG genotype, whereas a lower mineral content was related to the AA genotype. The TP53INP1 could be the candidate gene for sheep's mineral content.